2020
DOI: 10.1055/s-0040-1717152
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery Fellowship Website and Social Media Presence: Are Programs Optimizing Recruitment Strategy?

Abstract: Background Microsurgery fellowship applicants make decisions for future training based on information obtained from colleagues, mentors, and microsurgery fellowship program Websites (MFWs). In this study, we sought to evaluate the accessibility and quality of available information by microsurgery programs by analyzing the most commonly used web resources and social media outlets for applicants. Methods The San Francisco (SF) Match and American Society of Reconstructive Microsurgery Websites were quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…This is consistent with website analysis of other training programs. 1,16,20 When grouped by ERAS participation status, no statistically significant difference was found in the comprehensiveness of the websites' content. This indicates that there is a low-cost, low-risk window of opportunity for improvement for programs to attract better candidates across the USA.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This is consistent with website analysis of other training programs. 1,16,20 When grouped by ERAS participation status, no statistically significant difference was found in the comprehensiveness of the websites' content. This indicates that there is a low-cost, low-risk window of opportunity for improvement for programs to attract better candidates across the USA.…”
Section: Discussionmentioning
confidence: 92%
“…This observation was consistent over different geographic areas, as well as the ERAS participation status. 17,20 This study reveals that only 71.8% of the programs analyzed had basic information readily available on their websites, such as the number of fellow positions available per year. Other information, like salary, parking availability, or meal allowance was also hard to find or missing altogether.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study by Wang et al found that compared to the previous year, orthopedic surgery residency programs saw a 355% increase in social media use during the 2020-2021 application cycle [17]. Similar trends were seen for other specialties, including fellowships for other surgical subspecialties [18][19][20]. It is unclear why spine fellowship programs have opted to not use social media as a marketing and recruitment tool, as these platforms are effective for providing information to and connecting with potential applicants.…”
Section: Discussionmentioning
confidence: 99%
“…As social media and digital influence become more integrated into global culture, there has been a paradigm shift in residency recruitment methods. Many US residency programs across several specialties have expanded their websites and increased their social media presence [ 4 - 7 ].…”
Section: Introductionmentioning
confidence: 99%